Percentiles of gestational weight gain according to the pregestational body mass index and birth weight at the Honorio Delgado Hospital in Arequipa - Apaza Valencia, John (2017)
Objectives: To determine the gestational weight gain (GWG) percentiles according to pregestational body mass index (BMI) and birth weight at Honorio Delgado Hospital of Arequipa. Design: Descriptive observational study. Institution: Hospital III Honorio Delgado of Arequipa, Peru. Participants: Healthy pregnant women between 37 and 41 weeks of gestation who came to the hospital from July 2015 to June 2016 for delivery. Methods: Selection by systematic randomization of 1 007 pregnant women. Main outcome measures: The mean and percentiles of the total GWG were determined quarterly, monthly and weekly. Results: The 1 007 pregnant women had a mean maternal age of 26.7 years, a pregestational BMI of 25.7 and the average newborn weight was 3 456 g. According to the birth weight ranging from 2 780 to 3 820 g, the 25th and 75th percentile of the total GWG were 8.1 to 13.3 and 9.0 to 13.9 for low and normal pregestational BMI respectively, and the 25th and 50th percentiles were 7.3 to 10.0 and 4.5 to 8 kg respectively for overweight and obesity, respectively. Conclusions: The 25th and 75th percentiles of the total gestational weight gain were adequate for a low and normal pregestational body mass index, and the 25th and 50th percentiles corresponded to an overweight and obesity pregestational body mass index.